Digital counting of nucleic acid targets using solid-state nanopores. Issue 34 (24th August 2020) - Beamish, Eric; Tabard-Cossa, Vincent; Godin, Michel
Abstract : A nanostructure-based assay for miRNA detection and quantification using solid-state nanopores. Abstract : Assays targeting biomarkers for the early diagnosis of disease demand a sensing platform with a high degree of specificity and sensitivity. In this work, we developed and characterized a solid-state nanopore-based sensing assay for the detection of short nucleic acid targets with readily customizable nanostructured DNA probe sets. We explored the electrical signatures of three DNA nanostructures to determine their performance as probe sets in a digital counting scheme to quantify the concentration of targets. With these probes, we demonstrate the specific, simultaneous detection of two different DNA targets in a 2-plex assay, and separately that of microRNA-155, a biomarker linked to various human cancers. In addition to specific target detection, our scheme demonstrated the ability to quantify at least six different microRNA concentrations. These results highlight the potential for solid-state nanopores as single-molecule counters for future digital diagnostic technologies.